2005
DOI: 10.1128/jvi.79.5.3182-3186.2005
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 3a Protein Is a Viral Structural Protein

Abstract: The present study showed the association of a severe acute respiratory syndrome coronavirus (SCoV) accessory protein, 3a, with plasma membrane and intracellular SCoV particles in infected cells. 3a protein appeared to undergo posttranslational modifications in infected cells and was incorporated into SCoV particles, establishing that 3a protein was a SCoV structural protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
156
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 33 publications
6
156
1
1
Order By: Relevance
“…Since then, other publications have concurred in this observation and have shown that it is a structural protein (5)(6)(7)(8). ORF 3a is located between the S and E protein loci and encodes a protein of 274 aa.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Since then, other publications have concurred in this observation and have shown that it is a structural protein (5)(6)(7)(8). ORF 3a is located between the S and E protein loci and encodes a protein of 274 aa.…”
mentioning
confidence: 70%
“…The existence of 3a protein in both purified virus particles and virus-infected cell lysates has been reported (4,6). Few studies have shown that the 3a protein may be involved in cell apoptosis (15,16) and may be released from virus-infected cells or 3a proteintransfected cells (17).…”
Section: Sars-cov Is a Newly Identified Coronavirus In Humans That Lementioning
confidence: 99%
“…The 3a protein is associated with virus particles produced following infection of Vero E6 or Caco-2 cells (Ito et al, 2005;Shen et al, 2005) and can assemble into virus-like particles when co-expressed with the membrane and envelope proteins in insect cells (Shen et al, 2005). In vitro studies have also shown the 3a protein to interact with the viral envelope, membrane and spike proteins (Tan et al, 2004b;Tan, 2005) and the cellular protein caveolin-1 (Padhan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the prototypic coronavirus genes, the SARS-CoV genome also contains nine unique open reading frames (ORFs) (Marra et al, 2003). Of these, orf3a is the largest and encodes a protein of 274 aa, variously called ORF3A (Ito et al, 2005), X1 (Rota et al, 2003) or U274 (Tan et al, 2004b). The 3a protein has been predicted to contain an N-terminal signal peptide followed by three transmembrane domains and a C-terminal cytoplasmic domain of approximately 150 aa (Zeng et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation